2017
DOI: 10.3390/w9110838
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Spatial Interpolation of Precipitation for Hydrological Process Simulation in the Three Gorges Basin

Abstract: Accurate assessment of spatial and temporal precipitation is crucial for simulating hydrological processes in basins, but is challenging due to insufficient rain gauges. Our study aims to analyze different precipitation interpolation schemes and their performances in runoff simulation during light and heavy rain periods. In particular, combinations of different interpolation estimates are explored and their performances in runoff simulation are discussed. The study was carried out in the Pengxi River basin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
0
36
1
2
Order By: Relevance
“…In the hydrological simulation, the default spatial resolution of XRAIN data (250 m) was used as the input, and we used radar rainfall at different spatial resolutions without changing the optimized parameters for each event in the model to allow us to compare the results when using different resolutions. A number of interpolation techniques for reproducing the spatial continuity of rainfall fields have been described in the literature [6,18,[50][51][52][53][54][55]. These techniques are normally divided into two approaches: deterministic and geostatistical.…”
Section: Spatial Resolution Of Radar Rainfall Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In the hydrological simulation, the default spatial resolution of XRAIN data (250 m) was used as the input, and we used radar rainfall at different spatial resolutions without changing the optimized parameters for each event in the model to allow us to compare the results when using different resolutions. A number of interpolation techniques for reproducing the spatial continuity of rainfall fields have been described in the literature [6,18,[50][51][52][53][54][55]. These techniques are normally divided into two approaches: deterministic and geostatistical.…”
Section: Spatial Resolution Of Radar Rainfall Datamentioning
confidence: 99%
“…These techniques are normally divided into two approaches: deterministic and geostatistical. The most frequently used deterministic methods are nearest neighbor, inverse distance weighting, Thiessen polygon, and Kriging, which are fairly straightforward interpolation techniques that provide reliable results [18,[52][53][54]. Some studies also apply a geostatistical approach to interpolate the spatial and temporal resolution of the rainfall data [7,25].…”
Section: Spatial Resolution Of Radar Rainfall Datamentioning
confidence: 99%
See 1 more Smart Citation
“…There are 22 meteorological stations and 113 rain gauges located (see Figure 1) in or close to the TGRA, which were acquired from the National Meteorological Information Center and Hydrologic Statistical Yearbooks. Since the rain gauges only have rainfall data, other meteorological factors, including solar radiation, air temperature (maximum and minimum), relative humidity, and wind speed were interpolated from 22 meteorological stations to the 113 rain gauges by the Inverse Distance Weighted method introduced in our previous work [30]. The meteorological data were collected from 2009 to 2013.…”
Section: Data Collectionmentioning
confidence: 99%
“…Our previous research indicated that localized database and rational parameterizations of specific basins are required to improve the application of SWAT [2], and the finer the subdivision scheme and hydrologic response unit (HRU) definition, the better the model performance [29]. Obtaining more detailed precipitation data, based on the precipitation interpolation method, will improve the hydrological simulation performance of SWAT [30]. However, adapting SWAT in a large-scale region faced a trade-off involving the time used for the simulation and the description accuracy of natural characteristics [31][32][33].…”
Section: Introductionmentioning
confidence: 99%